2007
DOI: 10.1021/ie070778u
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the CO2Absorption Capacities in Aqueous 2-(2-Aminoethylamino)ethanol and Its Blends with MDEA and TEA in the Presence of SO2

Abstract: A study of carbon dioxide (CO2) and sulfur dioxide (SO2)/CO2 mixtures absorption has been carried out in aqueous 2-(2-aminoethylamino)ethanol (AEE) solution and its blends with N-methyldiethanolamine (MDEA) and triethanolamine (TEA) to estimate the influence of SO2, MDEA, and TEA on the CO2 absorption capacity of the AEE. The CO2 absorption loading has been estimated in 15 wt % AEE alone and in the presence of either 5 and 10 wt % MDEA or 5 and 10 wt % TEA solutions with 100 vol % CO2 and 5.03 and 15.02 vol % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…14 These studies (the relation between absorption rate and speciation during chemical absorption) are necessary to evaluate the aptitudes of amines to be used in carbon dioxide capture processes. The main part of the previous studies has only analyzed the absorption rate 1,5,6,8 but a complete characterization of the process is needed. The carbon dioxide absorption rate, the chemical reaction rate, the carbon dioxide loading (and the relation with reaction mechanism), and the ratio between carbon dioxide and amine concentration at the beginning of the process, can play a very important role in the election of a specific process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 These studies (the relation between absorption rate and speciation during chemical absorption) are necessary to evaluate the aptitudes of amines to be used in carbon dioxide capture processes. The main part of the previous studies has only analyzed the absorption rate 1,5,6,8 but a complete characterization of the process is needed. The carbon dioxide absorption rate, the chemical reaction rate, the carbon dioxide loading (and the relation with reaction mechanism), and the ratio between carbon dioxide and amine concentration at the beginning of the process, can play a very important role in the election of a specific process.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several technologies are available to reduce the carbon dioxide emission from industrial gas streams, but the chemical absorption with alkanolamines is the most widely used methodology. 2,3 This method is efficient and it usually allows the removal of a high percentage of the emitted carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies are available to reduce CO 2 emissions from industrial gas streams but the most effective one involves a liquid solvent which selectively captures the CO 2 through a molecular affinity (physical solvent) or a chemical reaction (chemical solvent). For instance, for low to moderate CO 2 pressures, chemical absorption with alkanolamines solutions usually permits the removal of 75%-90% of the CO 2 contained in the gas streams (Bonenfant et al, 2007). In order to find the most efficient solvents for CO 2 capture, there is therefore an increasing need to understand the mass transfer mechanisms occurring in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…25 2-(2-aminoethylamino)ethanol (AEE) solution and its blends with MDEA and TEA were used by Bonenfant et al to absorb CO 2 in the presence of sulfur dioxide (SO 2 ) to evaluate their influence on AEE's performance. 30 It was found that the presence of SO 2 lowers the CO 2 absorption rate and loading, while additions of ).…”
Section: Hybrid Absorbentsmentioning
confidence: 99%